2021
DOI: 10.26803/ijlter.20.12.15
|View full text |Cite
|
Sign up to set email alerts
|

Learning Potentials of Job Shadowing in Teacher Education

Abstract: This article dealt with the topic of practical training of students in teacher training programmes. Workplace learning represents an important contact between students and the world of work and can have several positive effects. In the text, we presented job shadowing as a possible learning activity that can complement other forms of practical training. The aim of the study was to identify the learning potential of this activity and how it should be structured to achieve this potential. Data were collected fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…This challenge takes the researchers to find a balanced approach for further improving education standards. As a result of this problem, one of the methods that have gained importance is job shadowing (Danijela, 2021). Understanding its relevance and novelty shows that job shadowing is a solid method to advance learning in career development.…”
Section: Introductionmentioning
confidence: 99%
“…This challenge takes the researchers to find a balanced approach for further improving education standards. As a result of this problem, one of the methods that have gained importance is job shadowing (Danijela, 2021). Understanding its relevance and novelty shows that job shadowing is a solid method to advance learning in career development.…”
Section: Introductionmentioning
confidence: 99%
“…The other related field in which job shadowing has been studied is K-12 teaching. Research has shown that job shadowing can relate to meaningful learning and the transfer of skills in teaching environments [10]. As covered in the following section, teaching is one of the core components of a job in academia.…”
Section: Job Shadowing In Other Fieldsmentioning
confidence: 99%